Polycyclic aromatic hydrocarbon exposure, miRNA genetic variations, and associated leukocyte mitochondrial DNA copy number: A cross-sectional study in China. (May 2020) - Duan, Xiaoran; Yang, Yongli; Zhang, Hui; Liu, Bin; Wei, Wan; Wang, Liuya; Sun, Changqing; Yao, Wu; Cui, Liuxin; Zhou, Xiaoshan; Wang, Wei
Abstract: Mitochondria DNA was preferentially attacked by the exogenous carcinogens including polycyclic aromatic hydrocarbons (PAHs) relative to nuclear DNA, and nuclear gene variants may account for variability in the mitochondrial DNA copy number (mtDNAcn). However, it remains unclear whether miRNA genetic variations are associated with mitochondrial DNA damage in the PAH-exposed workers. Therefore, we measured the leukocyte mtDNAcn, urinary 1-hydroxypyrene (1-OHPYR), environmental PAH exposure, and miRNA genetic polymorphisms among 544 coke oven workers and 238 healthy control participants. We found that the mtDNAcn in the exposure group (0.60 ± 0.29) was significantly lower than that in the control group (1.03 ± 0.31) ( t  = 18.931, P  < 0.001). Spearman correlation analysis showed that the peripheral blood leukocyte mtDNAcn had significantly negative correlations with the levels of 1-OHPYR and environmental PAH exposure ( P  < 0.001). Covariance analysis indicated that miR-210 rs11246190 AA, miR-210 rs7395206 CC, and miR-126 rs2297538 GG probably promoted a decrease in leukocyte mtDNAcn in the exposure or control groups ( P  < 0.05). In generalized linear model, miR-210 rs11246190 GG was a protective factor of mtDNAcn, and environmental PAH exposure was the risk factor of the mtDNAcn. In conclusion, the decrease of leukocyte mtDNAcn is the result of a combination of environmental and genetic factors. Graphical abstract: Image 1 Highlights: mtDNAcn decreased with environmental PAH exposure. miR-210 rs11246190 GG was a protective factor of mtDNAcn. The other 14 polymorphisms in miRNA had null effects on mtDNAcn.